PENGARUH STRUKTUR KEPEMILIKAN SAHAM PADA PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY - RUSTIARINI, NI WAYAN (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 6 No 1 (2011), 2011)
This research is aimed to investigate the influence managerial ownership,institutional ownership, and foreign ownership on corporate social responsibilitydisclosure. This research used Corporate Social Responsibility Index (CSRI) as ameasure of CSR disclosure, based on indicators from Bapepam regulation. Thesamples of this research are 56 manufacture firms listed in Indonesian StockExchange (IDX) at 2008.Test results show that managerial and institutional ownership do not havesignificant effect on CSR Disclosure, but foreign ownership have significant effecton CSR Disclosure. This indicated that foreign ownership structure in this studyhave concern with CSR disclosure to make investment decision.
Keywords: corporate social responsibility, foreign ownership, institusional ownership, managerial ownership.